MENINGKATKAN LAPORAN SPT TAHUNAN PPH PASAL 21 WAJIB PAJAK ORANG PRIBADI BAGI WARGA KECAMATAN LENGKONG BANDUNG - Ari Bramasto; Dudi Haryadi (SOSIOHUMANITAS, 2018)
Training for Filling Form in the Annual Income Tax Article 21 Individual Taxpayer Year 2017 is carried out in Lengkong District. This training aims to improve knowledge for residents about annual income tax reporting 21, especially in the Lengkong Subdistrict environment and from the training that improves knowledge of income tax reporting as provision for residents of Lengkong Bandung District aswell generally be able to keep track of the current tax developments.